2007
DOI: 10.1539/joh.49.242
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of EC‐SOD, Mn‐SOD and CuZn‐SOD in Rat Lung Exposed to Crystalline Silica

Abstract: SOD protein levels were also significantly lower than the control group at 90 and 180 d recovery. There was prominent EC-SOD immunostaining mainly in the plasma and alveolar macrophages and strong Mn-SOD staining in alveolar macrophages and interstitial cells of the proximal and distal portions of the alveolar duct following crystalline silica exposure. There was less CuZn-SOD staining in epithelial cells at terminal bronchioles in the crystalline silica-exposed group. These findings suggest that these SOD iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Our previous study using crystalline silica showed that even if the particles are of the same chemical composition, their biological effects vary depending on their particle size 4) . Hazard assessment of newly-generated respirable particles must therefore be conducted for such differences and various biomarker studies are currently being implemented to objectively and quantitatively assess the hazards of such substances [5][6][7][8][9][10][11][12][13][14] .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Our previous study using crystalline silica showed that even if the particles are of the same chemical composition, their biological effects vary depending on their particle size 4) . Hazard assessment of newly-generated respirable particles must therefore be conducted for such differences and various biomarker studies are currently being implemented to objectively and quantitatively assess the hazards of such substances [5][6][7][8][9][10][11][12][13][14] .…”
Section: Background and Objectivesmentioning
confidence: 99%
“…It catalyzes the dismutation of superoxide radicals into hydrogen peroxide and oxygen (11). EC-SOD is highly expressed in arteries (3,12), lungs, and airways (13,14), with high levels in alveolar macrophages (15). Human (16) and mouse studies (17)(18)(19) have shown that EC-SOD plays a key role in attenuating lung injury by blocking oxidative stressmediated lung inflammation; however, little is known about the role of EC-SOD in modulating allergic airway disease.…”
Section: Introductionmentioning
confidence: 99%
“…In lung disorders caused by dust, phagocytosis of dust induces infiltration of neutrophils and alveolar macrophages, and persistent or progressed inflammation is likely to cause lung injury and lead to irreversible changes, such as fibrosis and tumors (Nishi et al 2009; Borm and Driscoll 1996; Kim et al 2007). Persistent inflammation has been reported in an animal exposure model using asbestos and silica as materials known to have high toxicity (Fubini and Hubbard 2003; Schins 2002).…”
Section: Introductionmentioning
confidence: 99%